Correlation of serological markers and thrombocytopenia in early diagnosis of dengue infection - Ingale, Suchita Vikas; Upadhye, Aditi Jayant; Upadhye, Jayshree Jayant (International Journal of Research in Medical Sciences, 2018)
Background: Dengue is an acute viral infection with fatal complications. To reduce the disease burden, early and specific diagnosis of dengue hemorrhagic fever or dengue shock syndrome with supportive therapy reduces morbidity and mortality. This study was undertaken to evaluate the efficacy of NS1 antigen and platelet count. Methods: A total of 200 serum samples were collected from clinically suspected cases of dengue fever. Serum samples were tested for NS1, IgM and IgG and correlated with the platelet count. Results: Out of 200 samples screened in our study, 100 (50%) were positive for dengue parameters, 100 (50%) were negative. Out of 100 positive cases, 95 (95%) cases were positive for NS1antigen either alone or in combination with antibodies. 84 (84%) cases were exclusively positive for NS1 antigen only. Primary infection (positive for NS1 Ag, IgM, NS1 + IgM) was seen in 99 (99%) cases and secondary infection (positive for IgG, NS1 + IgG, IgM + IgG, NS1+ IgM+ IgG) was seen in 1 case (1%). Out of 100 positive cases, thrombocytopenia was observed in 60 (60%) of patients while 40 (40%) had platelet count within normal range. Conclusions: Dengue is endemic to Indian subcontinent. Currently no specific antiviral therapy is available. Measuring platelet count and detecting the NS1 antigen plays a vital role in early diagnosis, management and implementing the control measures in community to avoid spread of dengue.